Czy można poznać świadomość drugiego? Tło historyczno-filozoficzne koncepcji wczucia Edyty Stein - Mietelski, Tymoteusz (Warszawskie Studia Teologiczne, 2020)
The aim of this article was to present historical and philosophical background of Edith Stein’s concept of empathy. Stein based her PhD thesis on Husserl’s views and referred to actual state of research on possibility to know the consciousness of another. The author uses the hermeneutic method of analyzing Stein’swritings. He also examines Stein’s interpretation of approach of Husserl, Scheler,Lipps and other. In the result the relevance of Stein’s concept and its historical background were demonstrated